2020
DOI: 10.1111/evj.13352
|View full text |Cite
|
Sign up to set email alerts
|

Active immunisation against GnRH as treatment for unilateral granulosa theca cell tumour in mares

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…GnRH immunocastrates seem to be valuable material for future research on Leydig cell differentiation. Activation of the receptor by INSL3 induces differentiation of the gubernaculum, which pulls the testis caudally, thus driving the transabdominal phase of testicular descent [ 49 ]. Loss of Insl3 causes cryptorchidism, or retention of the testes in the body cavity, which is associated with low serum testosterone and infertility, as well as a higher risk of developing testicular tumors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…GnRH immunocastrates seem to be valuable material for future research on Leydig cell differentiation. Activation of the receptor by INSL3 induces differentiation of the gubernaculum, which pulls the testis caudally, thus driving the transabdominal phase of testicular descent [ 49 ]. Loss of Insl3 causes cryptorchidism, or retention of the testes in the body cavity, which is associated with low serum testosterone and infertility, as well as a higher risk of developing testicular tumors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 While the trial was not systematically designed and the hormonal results were not conclusive, the owners of all four mares reported the cessation of the abnormal behaviours (predominantly aggression or stallion-like), while ultrasonographic examinations revealed no changes in ovarian size. 27 GnRH vaccines, which can be used with adjuvants, may suppress reproductive cyclicity with a very variable time to return to cycling. 2,3,28 Despite the lack of ovarian activity, however, it is reported that despite use of these vaccines some mares can continue to exhibit oestrus behaviours, often in irregular or continuous patterns.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, a nonsurgical approach was used to treat four mares with presumed GCTs using multiple injections of the GnRH vaccine 27 . While the trial was not systematically designed and the hormonal results were not conclusive, the owners of all four mares reported the cessation of the abnormal behaviours (predominantly aggression or stallion‐like), while ultrasonographic examinations revealed no changes in ovarian size 27 . GnRH vaccines, which can be used with adjuvants, may suppress reproductive cyclicity with a very variable time to return to cycling 2,3,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Mannose-modified nanoparticles can effectively improve the delivery efficiency of tumor antigen. These nanoparticles act as carriers that can stably load tumor antigens and release them into the tumor microenvironment [190]. Antigen-presenting cells (such as dendritic cells) take up and process these tumor antigens before presenting them to T cells and inducing an immune response to the tumor antigen.…”
Section: Activation Of T Cells By Mannose Modified Lipid Calcium Phos...mentioning
confidence: 99%